Design of insulin-loaded alginate nanoparticles: Influence of the calcium ion on polymer gel matrix properties - Reis, Catarina P. (2006)
Alginate-based nanoparticles were produced by dispersing alginate aqueous solution containing an insoluble calcium salt within mineral oil forming a water-in-oil emulsion. Subsequently, alginate gelled upon contact with the calcium ions due to the physical cross-linking between the carboxylate anions of the alginate and the calcium ions. The influence of the calcium salt, added in varying amounts, on gel integrity and on particle size was investigated. The efficiency of encapsulating active biological compounds by nanoparticles was also assayed. The calcium concentration was seen to be a crucial parameter in particle production, influencing the particle size, the viscosity of the solutions at different stages of the emulsification/gelation process and, finally, the encapsulation efficiency. The most appropriate mass relation between calcium and alginate was 7% (w/w). Under this condition, the smallest mean diameter obtained was 2.604 ± 2.141 pm combined with the narrowest range of particle sizes. The encapsulation efficiency of insulin was over 71%. These previous characteristics appear to be best suited for producing small, well-dispersed and stable nanoparticles with high encapsulation of insulin. This particulate system may be considered as a promising carrier for the oral delivery of insulin.